Kewenangan dan Peran Majelis Kehormatan Notaris dalam Upaya Perlindungan Hukum terhadap Proses Penegakan Hukum yang Melibatkan Notaris: Studi Kasus Putusan Nomor 13/G/2018/PTUN-TPI - Permata Aisyiah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
A notary as a public official must maintain the confidentiality of deeds and protocols but is often involved in law enforcement processes. Law Number 2 of 2014 establishes the Notary Honorary Council (MKN), authorized to approve summons and access to original deeds. This study applies normative legal research with statutory, conceptual and case approaches based on Decision 13/G/2018/PTUN-TPI, supported by interviews. Findings show MKN functions preventively and protectively to balance law enforcement and notarial dignity. The administrative court confirms MKN approval as an administrative decision subject to review, yet unclear criteria and time limits still create legal uncertainty.